T Cell Receptor Alpha Chain Genes in the Teleost Ballan Wrasse (Labrus bergylta) Are Subjected to Somatic Hypermutation - Bilal, Sumaira; Lie, Kai Kristoffer; Sæle, Øystein; Hordvik, Ivar (Frontiers in Immunology, 2018)
Previously, somatic hypermutation (SHM) was considered to be exclusively associated with affinity maturation of antibodies, although it also occurred in T cells under certain conditions. More recently, it has been shown that SHM generates diversity in the variable domain of TCR in camel and shark. Here we report somatic mutations in TCR alpha chain genes of the teleost fish, Ballan wrasse (Labrus bergylta), and show that this mechanism adds extra diversity to the polymorphic constant (C) region as well. The organization of the TCR alpha/delta locus in Ballan wrasse was obtained from a scaffold covering a single copy C alpha gene, 65 putative J alpha segments, a single copy C delta gene, one J delta segment and two D delta segments. Analysis of 37 fish revealed 6 allotypes of the C alpha gene, each with 1 – 3 replacement substitutions. Somatic mutations were analyzed by molecular cloning of TCR alpha chain cDNA. Initially, 79 unique clones comprising four families of variable (V) alpha genes were characterized. Subsequently, a more restricted PCR was performed to focus on a specific V gene. Comparison of 48 clones indicated that the frequency of somatic mutations in the VJ region was 4.5/1000 bps, and most prevalent in complementary determining region 2 (CDR2). In total, 45 different J segments were identified among the 127 cDNA clones, counting for most of the CDR3 diversity. The number of mutations in the C alpha chain gene was 1.76 mutations/1000 bps and A nucleotides were most frequently targeted, in contrast to the VJ region where G nucleotides appeared to be mutational hot spots. The replacement/synonymous ratios in the VJ and C regions were 2.5 and 1.85, respectively. Only 7% of the mutations were found to be linked to the activation-induced cytidine deaminase (AID) hotspot motif (RGYW/WRCY).